Aging, Exercise, and Injury: Integrative Approaches for Maintaining Mobility and Preventing Falls - Ahmadpour, Mobina; Tatar, Sogand; Bragazzi, Nicola Luigi (International Journal of Sport Studies for Health, 2025)
Objective: This study aims to explore integrative strategies for maintaining mobility and preventing falls in older adults by synthesizing evidence on exercise-based and multidisciplinary interventions. Methods and Materials: This narrative review employed a descriptive analysis approach to examine literature published between 2018 and 2024. Studies were identified through comprehensive searches in academic databases including PubMed, Scopus, Web of Science, and ScienceDirect, using keywords related to aging, mobility, exercise, and fall prevention. Selected articles focused on individuals aged 60 and older and addressed one or more relevant domains, including strength, balance, aerobic and flexibility training, environmental and behavioral interventions, medication and sensory management, nutritional support, and psychological strategies. A total of 58 peer-reviewed articles were reviewed and categorized into thematic areas to identify evidence-based practices and gaps. Findings: Aging is associated with declines in muscle strength, balance, proprioception, gait, and cognitive function, all of which contribute to increased fall risk. Exercise-based interventions, particularly those targeting strength, balance, and coordination, are effective in enhancing mobility and reducing falls. However, integrative approaches that also address environmental hazards, medication-related risks, sensory impairments, nutritional deficiencies, and psychological barriers yield more comprehensive outcomes. Barriers such as socioeconomic status, chronic illness, low motivation, and limited access to services hinder implementation, while facilitators like caregiver involvement, community-based programs, and telehealth enhance adherence. Personalized, adaptable, and culturally sensitive programs are essential for long-term engagement and effectiveness. Conclusion: Preventing falls and maintaining mobility in older adults requires a multidimensional strategy that goes beyond exercise alone. Integrative approaches that combine physical training with medical, environmental, nutritional, and psychological components are more effective in addressing the complex nature of fall risk. Future research should focus on tailoring interventions to diverse populations, leveraging technology, and embedding fall prevention into routine healthcare and community settings.